Numerical Modelling of Cylindrical Fluid Filled Tank - Kotrasová, Kamila; Frantík, Petr; Kormaníková, Eva (WSEAS, 2024)
The demand for drinking and service water storage is rising with changing climate conditions and increasing life expectancy. The tanks are commonly used to store large volumes of liquids and materials in various fields of the economy. This paper presents the model of the numerical simulation for the steel tank filled with fluid, using the finite element method. The results of the tank filled with water are presented, by the results: the pressure of the fluid the effective stress, and the maximum deformation of the tank solid domain. The correctness of the pressure values was verified by the simple calculation of the fluid pressure. Finally, the paper documents the results for various fluid fillings with a considered range of fluid densities. The influence of the fluid filling height on the behavior of the solid domain of the fluid filling container loaded by the static loading as well as the effect of the width of the tank on the behavior of the solid domain of the fluid filling container. © 2024, World Scientific and Engineering Academy and Society. All rights reserved.

The demand for drinking and service water storage is rising with changing climate conditions and increasing life expectancy. The tanks are commonly used to store large volumes of liquids and materials in various fields of the economy. This paper presents the model of the numerical simulation for the steel tank filled with fluid, using the finite element method. The results of the tank filled with water are presented, by the results: the pressure of the fluid the effective stress, and the maximum deformation of the tank solid domain. The correctness of the pressure values was verified by the simple calculation of the fluid pressure. Finally, the paper documents the results for various fluid fillings with a considered range of fluid densities. The influence of the fluid filling height on the behavior of the solid domain of the fluid filling container loaded by the static loading as well as the effect of the width of the tank on the behavior of the solid domain of the fluid filling container. © 2024, World Scientific and Engineering Academy and Society. All rights reserved.
Numerical Modelling of Cylindrical Fluid Filled Tank
Keywords: analysis; density; FEM; Fluid; static; tank; analysis; density; FEM; Fluid; static; tank